Penerapan Ketrampilan Mengajar Guru Pendidikan Agama Kristen di Jenjang Sekolah Dasar - Femike Sinadia; Jeane M. Tulung; Deflita Lumi (Peneliti.net, 2021)
The purpose of this study was to describe and analyze the application of the teaching skills of Christian Religious Education teachers, especially in the mastery of teaching materials and the use of learning methods, supporting and inhibiting factors as well as the efforts made. This research is a qualitative research, which will be conducted in elementary schools in 2021. Data was collected through observation, interviews and documentation. Informants are classroom teachers, Christian Religious Education teachers, school principals, and students. The results of this study showed that 1) The application of teaching skills of Christian Religious Education teachers, especially in the mastery of learning materials had been applied well to low and high grades, 2) The use of learning methods had not been fully applied to low and high grades, 3) Supporting factors in control of teaching materials, namely textbooks, supporting books, libraries, 4) Supporting factors in the use of methods that are suitable for classrooms, school yards, student textbooks, book guides, computers, and LCDs, 5) Inhibiting factors in mastering basic materials, namely limitations teacher manuals and lack of teacher preparation, 6) Inhibiting factors in the use of suitable methods, namely the lack of teacher knowledge of learning methods, 7) Efforts made to overcome obstacles in controlling learning materials and the use of methods used, namely teachers must develop themselves by how to take training for to develop its potential. From these results, it is recommended that schools maintain the maintenance of learning inventories, complement the needs of teachers by providing, so that Christian Religious Education teachers focus on their main tasks. Christian Religious Education teachers must be more creative and need to attend training to develop their potential.